Problem amortyzacji budynków i budowli w państwowych szkołach wyższych - Ćwiąkała-Małys, Anna; Małys, Krzysztof (A Problem of the Depreciation of Buildings and Building Structures in High Public Schools, 2005)
The financing of fixed assets in a high public school has a form of the purposive investment endowments.Buildings and building structures of a high public school are not depreciated. A decline inthe value of high public school's assets are not connected with an accumulating of means which allowsto reproduce the assets. Therefore the didactic expenses are lowered in value by an amount ofdepreciation. This situation indirectly affects the lowered expenses of education. In long run thedepreciation of buildings and building structures should be included in expenses of education. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 296-300